The Effects of Urbanization on the Infant Gut Microbiota and Health Outcomes - Brushett, Siobhan; Sinha, Trishla; Reijneveld, Sijmen A.; de Kroon, Marlou L. A.; Zhernakova, Alexandra (Frontiers in Pediatrics, 2020)
Humans and their gut microbiota have co-evolved over thousands of years, resulting in the establishment of a complex host–microbiota ecosystem. Early life environmental factors, such as delivery mode, nutrition and medication use, have been shown to substantially affect both host–microbiota interactions and health outcomes. However, the effects of urbanization (characterized by the spectrum of rural and urban populations) on these early life events have been overlooked. A deeper understanding of the relationship between urbanization and microbiota development will allow for the identification of novel biological and social approaches that can be implemented to prevent and treat disease and promote maternal and infant/child health. The aim of this review is to summarize how factors associated with urbanization differentially impact delivery mode, nutrition and medication use, and how these changes subsequently affect the gut microbiota and health outcomes of infants. This review also describes the important evidence gaps associated with these relationships and recommends actions that can be taken to improve the health of mothers and infants worldwide.